The quintland sisters : a novel - Wood, Shelley (New York, NY : William Morrow, an imprint of HarperCollinsPublishers, 2019)
Teenaged midwife Emma Trimpany attends the birth of the Dionne quintuplets in 1934 Ontario and becomes their nurse when they are removed from their family and into government custody, witnessing their exploitation as curiosities.
Includes bibliographical references (pages 443-444).
Keywords: Dionne quintuplets -- Fiction; Quintuplets -- Fiction; Midwives -- Fiction; Dionne quintuplets -- Fiction; Quintuplets -- Fiction; Midwives -- Fiction; Diaries -- Fiction; Diary fiction; Historical fiction; Historical fiction